Asas Peradilan Cepat Dalam Pengadilan Hubungan Industrial: (Studi Lokasi Pengadilan Hubungan Industrial Yogyakarta) - Puti Mayang Seruni (UIR Law Review, 2019)
This legal research aims to identify the relation between the speedy administration of justice  in the industrial relations court and the implementation of the time limit for termination of employment relationship cases at the Yogyakarta industrial relations court in 2017 with the speedy administration of justice  and the legal consequences if the time limit provisions cannot be met. This legal research is a empirical research that used primary and secondary data obtained from literature and field research. There are 3 (three) conclusions that can be drawn from the result of this research. First, the application of the speedy administration of justice  in the industrial relations court can be found in art Number 2 of 2004 on Industrial relations dispute settlement act, which must be resolved within 50 days since the first trial. Second, the implementation of the time limit for termination of employment relationship cases at the Yogyakarta industrial relations court in 2017 is sufficient in accordance with art Number 2 of 2004 on Industrial relations dispute settlement act, as many as 6 out of 11 cases can be completed on time. Third, there are no legal consequences that occur if the time limit provisions cannot be met.